Vaccine development and deep immune profiling in preclinical models of emerging outbreak viral pathogens - Purushotham, JN (2022)
Emerging outbreak viral pathogens pose a significant threat to public health. Essential studies on the pathogenesis of and preventive tools for infectious threats often rely upon preclinical models to inform or supplant evaluations in humans. This thesis features studies characterising the immune responses after vaccination and infection in animal models, ranging from rodents to non-human primates, with a focus on two viral pathogens of epidemic/pandemic potential: Lassa virus (LASV) and severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2).